Splošne predpogodbene dolžnosti informiranja - Fakin, Andreja (Podjetje in delo, 2015)
Pre-contractual information duties obliging the contracting party to disclose information relevant for formation of a contract have not been in the spotlight of the Slovenian legal theory yet. Though in Slovenia the institute of general pre-contractual information duties has been recognized as an institute originating from the principle of good faith, it has yet not become fully used and accepted in the legal practice. The reason for such situation is that the cases which are substantially placed in the scope of resolving the allocation of information burden between parties are not solved through the institute of pre-contractual information duties, unless these duties are explicitly determined by law. To ensure the opportunity for the improvement of the institute and to be more frequently and correctly used in legal practice, this article focuses on additional explanation and justification of theoretical grounds on which the use of the institute and its existence is built on: the principle of good faith combined with the institute of mistake, deception and usury. Next to that, it is also trying to discover whether and what kind of possibilities for expanding the pre-contractual liability exist.
Keywords: informiranje; odgovornost; pogodbe; pogodbeno pravo; poštenost; prevare